Pengaruh Kualitas Pelayanan Jasa Transportasi Terhadap Kepuasan Konsumen Armada Bus Transzentrum Madu Kismo Di Kabupaten Grobogan - Supriyanti, Rita, Dra. Hj Umrotun, M.Si, Dra.Hj Retno Woro Kaeksi, M.Si (2017)
This study entitled "Effect of Service Quality Customer Satisfaction Transportation Bus Fleet TransZentrum Honey Kisma In Grobogan". The purpose of the first study, to determine the effect of tangible (physical evidence) that consists of the cleanliness of buses, AC buses, appearance of employees, waiting rooms and facilities, engine and bus body on consumer satisfaction Trans Zentrum Bus. Second, to megetahui the influence of reliability (confidence) that consists of timeliness, reliability of the bus crew, the readiness of employees in serving the customer satisfaction Trans Zentrum Bus. The third, to investigate the influence responsiveness (responsiveness) which consists of the willingness of the crew bus, the bus crew alertness, the ability of the crew bus to customer satisfaction Trans Zentrum Bus. Fourth, to investigate the influence assurence (collateral), which consists of security and comfort, the needs of the hospitality crew bus, courtesy bus crew on consumer satisfaction Trans Zentrum Bus. Fifth, to determine the effect of empathy (empathy), which consists of the ease of information, the bus crew to maintain communication with the consumer, the bus crew understand the needs of consumers on consumer satisfaction Trans Zentrum Bus. Sixth, to determine the influence aanya tangible (physical evidence), reliability (trust), responsiveness (responsiveness), assurance (assurance), an empathy (empathy), which jointly influence consumer satisfaction Trans Zentrum Bus. The method used in this study with the primary and secondary data analysis, while the methods used for data collection of this study using questionnaires, observation, library research. Of the 100 respondents selected using samplinge accidental obtained some research results. The results showed that the quality of service consisting of tangiable, reliability, responsiveness, assurance, and empathy simultaneously (one by one) and partial (together) significantly affects customer satisfaction TransZentrum bus. Determination test results showed that 69.4% of service quality affects customer satisfaction TransZentrum Bus company.